(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Substantivization, the process by which adjectives assume the role of nouns, is a significant phenomenon in English linguistics. This transformation allows adjectives to function as nominal elements in sentences, carrying syntactic and semantic weight similar to that of nouns. The process enriches language by creating concise expressions and facilitating stylistic diversity. This article explores the linguistic principles, functions, and examples of substantivization in English, emphasizing its relevance in grammar and discourse.